Self-Care Adherence Among Tuberculosis Patients In Tasikmalaya City - Lilis Lismayanti; Asita Elengoe; Tukimin Bin Sannsuwito; Falah, Miftahul (Sahabat Publikasi Kuu, 2024)
Mycobacterium tuberculosis is the infectious agent that causes tuberculosis (TB), a communicable disease. Patients with tuberculosis (TB) experience sadness as a result of words they hear regarding the spread of the disease, which can lead to stress and unfavorable opinions. Investigating self-care adherence among TB patients at the Tamansari Public Health Center in Tasikmalaya City, Indonesia, was the goal of this study. The study's participants were the TB patients at Tamansari Public Health Center. With a total sampling technique, the sample size was 56 responders. The descriptive method was used in this study. The majority of TB patients had good self-care adherence, according to the research findings. In conclusion self-care adherence among TB patients were good enough to prevent TB disease. The results of this research are expected to play a role in providing health education and self-care to sufferers to eliminate TB.